2008
DOI: 10.1299/jfst.3.999
|View full text |Cite
|
Sign up to set email alerts
|

Development of Diffuser/Nozzle Based Valveless Micropump

Abstract: A valveless micropump was realized with a diffuser/nozzle shaped channel and a variable volume actuator which produces an oscillating flow. One-way flow may be realized in the nozzle direction since the pressure loss in a nozzle channel is lower than that in a diffuser channel. Pump characteristics were measured for various angles of a diffuser/nozzle element and positions of the actuator to investigate the effect of pump geometry on characteristics. The experimental results showed an optimal diffuser/nozzle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…This is in contradiction with the results of the steady flow regime where g decreases with increasing Re. • For the total pump, net flow rate increases with increasing Re, regardless the diffuser angle (Tanaka et al 2008;Sheen et al 2008;Hwang et al 2008). …”
Section: Effects Of Reynolds Numbermentioning
confidence: 95%
See 2 more Smart Citations
“…This is in contradiction with the results of the steady flow regime where g decreases with increasing Re. • For the total pump, net flow rate increases with increasing Re, regardless the diffuser angle (Tanaka et al 2008;Sheen et al 2008;Hwang et al 2008). …”
Section: Effects Of Reynolds Numbermentioning
confidence: 95%
“…They found that net flow rate increased rapidly with increasing frequency, and reached the peak at f = 250 Hz, then decreased slowly with further increase in frequency. Tanaka et al (2008) developed a valveless micropump with a diffuser/nozzle shaped channel and a variable volume actuator which produced an oscillating flow. They measured the micropump characteristics for various angles of the microdiffuser (10°B h B 90°) and frequencies of the actuator (20 Hz B f B 140 Hz).…”
Section: Flow Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other contributions to the optimization of the nozzle/diffuser performance have been carried out numerically and experimentally over the last decade (e.g. [8,[12][13][14][15][16][17][18][19][20][21][22]). Gerlach and Wurmus [23] studied a piezoelectrically driven micropump in which a nozzle/diffuser valve was incorporated and concluded that the device could be used as a mixer/reactor chamber, in addition to operating as a micropump, due to the turbulence that was generated during its operation.…”
Section: Introductionmentioning
confidence: 99%
“…However, moving parts are prone to wear and difficult to manufacture. Besides, the movement of the passive valve and the volume change of the pump chamber are out of sync at high excitation frequency (Tanaka and Tsukamoto 2008). The mechanism of valveless piezoelectric micropump is based on the flow characteristics in the special tubes and avoid the disadvantages of the piezoelectric micropumps with valves.…”
mentioning
confidence: 99%